PENGARUH PENDIDIKAN DAN PELATIHAN SERTA KOMPETENSI TERHADAP KINERJA PERSONIL MELALUI KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (STUDI PADA SATUAN RESERSE KRIMINAL POLRES KENDARI) - Dyon Zionissa; Nurwati Nurwati; Rahmat Madjid; Wahyuniati Hamid (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
The research was carried out with the aim of knowing 1) the effect of education and training on organizational commitment, 2) the effect of competence on organizational commitment, 3) the effect of education and training on personnel performance, 4) the effect of competence on personnel performance, 5) the effect of organizational commitment on personnel performance. , 6) the effect of education and training on personnel performance through organizational commitment, and 7) the effect of competence on personnel performance through organizational commitment. The object of this research is the Criminal Investigation Unit of the Kendari Police. Primary data was obtained through the distribution of 42 questionnaires to all members of the Criminal Investigation Unit of the Kendari Police and then processed with the PLS software application